Bacteriological analysis of donor human milk in milk bank in an Indian setting - Singh, Poonam H; Surana, Amita Uday; Chaudhari, Vaishali (Indian Journal of Child Health, 2017)
Background: Although human milk banking in India was started in 1984, limited data regarding bacteriological quality of milk are available. Objective: To find bacteriological contamination of milk samples in human milk bank. Methods: Retrospective analysis of milk samples from milk bank for the year 2009-2015 was done. Group A donor mothers were from postnatal or neonatal units of our hospital. Group B mothers were from milk donation camps organized at the community level. All milk samples were plated on blood agar for bacteriological analysis. Pre-pasteurized samples were analyzed for the year 2014-2015 only. Results: Total donor mothers were 3670. 1481 (40%) were from milk donation camp at the community level. 327 (9%) were preterm milk. 2.34% of post-pasteurized samples showed contamination as compared to 9.1% pre-pasteurized milk samples (p=0.002). Group A mothers showed a higher contamination rate as compared to Group B mothers in both pre-pasteurized (p<0.001) and post-pasteurized samples (p=0.006). The most common organisms isolated in pre-pasteurized samples were Gram-positive bacilli (51.89%), coagulase-negative staphylococci (CONS, 44.96%), and Gram-negative bacilli (3%). The most common organisms in post-pasteurized samples were Gram-positive bacilli (88.23%) and CONS (11.76%). No Gram-negative bacilli were isolated from post-pasteurized samples. Conclusion: Contamination rates in our study for both pre- and post-pasteurized samples are quite low as compared to other studies. Community collection of human milk was safe with regard to bacteriological contamination. Holder’s method of pasteurization is effective in reducing contamination.